Head-to-head comparison of the Lyon Schuss and fixed flexion radiographic techniques. Long-term reproducibility in normal knees and sensitivity to change in osteoarthritic knees. Issue 11 (7th February 2008) - Le Graverand, M-P Hellio; Vignon, E P; Brandt, K D; Mazzuca, S A; Piperno, M; Buck, R; Charles, H C; Hunter, D J; Jackson, C G; Kraus, V Byers; Link, T M; Schnitzer, T J; et al.
Abstract : Objective: The Lyon Schuss (LS) and fixed flexion (FF) views of the knee are superior to a conventional standing anteroposterior view in evaluating joint space narrowing (JSN) in osteoarthritis (OA). Both position the knee identically but only the LS aligns the medial tibial plateau (MTP) with the x -ray beam fluoroscopically. The present study provides the first head-to-head comparison of the LS and FF views. Methods: At baseline and 12 months, 62 OA and 99 control knees were imaged twice on the same day with LS and FF views. Minimum joint space width (mJSW) was measured by computer and MTP alignment was assessed from the distance between anterior and posterior margins of the MTP (intermargin distance, IMD). Reproducibility of measurements of mJSW and sensitivity to change were evaluated. Results: In normal knees, JSW did not vary over 12 months with either view. In OA knees, 12-month mJSN was 0.22 (0.43) mm with the LS view and −0.01 (0.46) mm with the FF view (p = 0.0002 and p = 0.92, respectively). Mean IMD was only half as large in LS as in FF views (0.9 (0.5) mm vs 1.9 (1.2) mm, p<0.0001). Conclusions: LS and FF radiographs offer similar reproducibility in JSW measurement. However, presumably due to its superiority in aligning the MTP, the LS view is much more sensitive to JSN in OA knees.